ARTIFICIAL INTELLIGENCE AND BLOCKCHAIN TECHNOLOGY FOR SECURE DATA AND PRIVACY - Abdul Hannan, Shaikh (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2023)
Data, which is then processed in order to extract the desirable characteristics, serves as the input for a number of different AI algorithms. However, the facts that can be found on the internet are incredible and tough to authenticate. Given the complexity of the internet, it is quite challenging to validate the data for the consumers. Consequently, in this research, we suggested using SecNet as a solution. An architecture that assists in the protection of data storage, the processing of data, and the sharing of large-scale Internet settings is known as SecNet. The primary objective of this architecture is to enhance the performance of artificial intelligence algorithms across a variety of data sources in order to provide a cyberspace that is more safe and to make use of actual big data. This architecture combines and supplies the following three primary components: 1) The trading of data based on a blockchain is carried out with the ownership of the data being assured. This enables the interchange of accurate data in a wide-ranging environment and contributes to the formation of actual "big data. 2) The protection of an AI-based secure computing platform that is powered by artificial intelligence to develop more astute security standards and contribute to the establishment of a cyberspace that is more reliable. 3) The trustworthy value-sharing Security Service buy Mechanism gives participants a fantastic opportunity to gain Economic Rewards for the provision of data or services, which makes data sharing easier and ultimately leads to improved AI performance".